Ductile behaviour of oil palm shell concrete slabs subjected to blast loads - Alengaram, Ubagaram Johnson; Mohottige, H.W.N.; Wu, C.Q.; Jumaat, Mohd Zamin; Yap, Soon Poh; Wang, Z.Q. (2016)
Oil palm shell (OPS) is an industrial waste material abundantly available in Malaysia and other South East Asian countries. It has high aggregate impact resistance characteristics and hence its capability to withstand blast load was tested through OPS concrete (OPSC) slabs designed and developed in University of Malaya, Kuala Lumpur, Malaysia and tested at Huluduo, China. LVDTs, pressure transducers and accelerometers were used to record data of response of the slabs subjected to quasi-static load and blast loads of 1, 5 and 10 kg TNT. The recorded data were then analysed and compared and conclusions were made on the effectiveness of OPS as a coarse aggregate. It has been found that OPSC outperformed normal concrete (NC) slab when subjected to 10 kg TNT as OPSC panel was intact and had no shrapnel; the ductility behaviour of OPSC, it exhibited multiple cracks and the impact resistance of OPS through its energy absorption due to fibrous content within OPS itself was visible both in crack pattern and in its propagation. Though OPS is of organic nature, its resistance to blast waves was observed as the huge fire ball created due to blast had no or little effect on the OPSC panels.